Cytologic findings of spindle epithelial tumor with thymus‐like elements. (29th November 2017) - Baste Subia, Maria N.; Digoy, Paul; Hum, Martina; Yu, Zhongxin; Conrad, Rachel
Abstract : Spindle epithelial tumor with thymus‐like elements (SETTLE) is a rare and morphologically unique biphasic pediatric thyroid tumor of low malignant potential. There are less than 50 cases reported in the literature and few reported metastases. Despite the common usage of needle aspiration for thyroid and lymph node evaluation, cytologic descriptions of SETTLE are rare and tend to focus on a hypercellular biphasic appearance. We report aspirate findings of early cystic lymph node metastases in a 14‐year‐old girl, showing abundant matrix and low cellularity. We propose that the lack of recognition of this abundant matrix and cystic ultrasound appearance (as well as rarity of this tumor) may account for the low number of cytologic descriptions in the literature. Improved recognition may lead to increased usefulness of aspiration in the diagnosis and follow‐up of SETTLE. Laryngoscope, 128:E78–E82, 2018